Hurdles and steps: Estimating demand for solar photovoltaics - Kenneth Gillingham; Tsvetan Tsvetanov (Quantitative Economics, 2019)
This paper estimates demand for residential solar photovoltaic (PV) systems using a new approach to address three empirical challenges that often arise with count data: excess zeros, unobserved heterogeneity, and endogeneity of price. Our results imply a price elasticity of demand for solar PV systems of −0.65. Counterfactual policy simulations indicate that reducing state financial incentives in half would have led to 9% fewer new installations in Connecticut in 2014. Calculations suggest a subsidy program cost of 364/tCO2 assuming solar displaces natural gas. Our Poisson hurdle approach holds promise for modeling the demand for many new technologies.
Keywords: C33; C36; Q42; Q48; 330; Count data; hurdle model; fixed effects; instrumental variables; Poisson; energy policy